Research on the Innovation of Online and Offline Mixed Teaching Reform of Ideological and Political Courses in Universities in the New Era - Cao , Bo (Journal of Theory and Practice of Management Science, 2023)
In university courses, ideological and political courses are very important for cultivating students' outlook on life and values. Teachers should combine the main situation of ideological and political courses in universities, innovate teaching models, further ensure students' ideological and moral levels, and improve the quality of talent cultivation in all aspects. Teachers should combine the personal characteristics of students to construct a mixed online and offline teaching mode for ideological and political courses in universities, select scientifically appropriate textbooks, and build and improve the teaching resource library, in order to better ensure the smooth implementation of teaching activities and form an education system that meets teaching objectives. This article will mainly discuss the relevant content of ideological and political courses in universities.